Pengaruh Harga dan Fasilitas Terhadap Loyalitas Pelanggan Melalui Kepuasan Sebagai Variabel Intervening Pada Member Velcro Gym Kota Jambi - Nicholas Raymond Sentosa; Yossinomita Yossinomita; Ayu Feranika (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The fitness industry has shown rapid growth as public awareness of the importance of healthy lifestyles increases in today's world. Gyms no longer function solely as a place to exercise, but also offer value and a sustainable experience for their members. The ability to manage a gym and retain members in this increasingly competitive era encourages gym owners to be more sensitive to factors that could potentially affect member satisfaction and loyalty. To improve the quality of the gym, it is necessary to evaluate the price and quality offered in the form of well-maintained and complete facilities. The suitability of the price to the benefits felt by members will make them more loyal to training at the gym. Likewise, comfortable facilities can increase member loyalty, which in turn drives member satisfaction, especially at Velcro Gym.